She dies tomorrow - Seimetz, Amy 1981-; Keitel, Jay; Sheil, Kate Lyn 20. Jh; Adams, Jane 1965-; Audley, Kentucker 1981- (Radiance Films, 2023)
"Eine junge Frau ist überzeugt davon, dass sie innerhalb der nächsten 24 Stunden sterben wird. Ihre Todesangst breitet sich wie eine Epidemie immer weiter aus, befällt ihre Freunde und deren Familien. Der existenzialistische Psychothriller hinterfragt die Verdrängung der Sterblichkeit aus gesellschaftlichen und persönlichen Diskursen, liest dieses Tabu als psychologische Infektionskette und verfolgt diese in aneinandergereihten Miniaturen, ohne die Fragestellung aufzulösen. Ein im besten Sinne unangenehmer Film mit nuancierten Hauptdarstellerinnen." [filmdienst.de]
Original: USA 2020
Blu-ray limited edition special features: High-Definition digital transfer approved by writer-director Amy Seimetz ; original 5.1 DTS-HD Master Audio surround sound ; A ‘Making of’ featurette with Seimetz and cinematographer Jay Keitel (2020, 23 mins) ; newly filmed interviews with stars Kate Lynn Sheil and Jane Adams (2022, 13 mins) ; She dies tomorrow and The viral apocalypses of the future: A visual essay on contagion in modern horror by Anton Bitel (2022, 15 mins) ; audio commentary by critic and programmer Anna Bogutskaya ; original trailer ; reversible sleeve featuring original and newly commissioned artwork by Time Tomorrow ; limited edition 28-page booklet featuring new writing on the film by Lillian Crawford and Isabel Millar and an interview with Seimetz from the original press book
Bildformat 1.78:1
Keywords: Film; Blu-Ray-Disc